First record of Lindernia dubia (Linderniaceae) in India and reduction of Lindernia nelliyampathiensis as one of its synonyms - Prasad, Mangavayal Govindan; Sunojkuma, Purayidathkandy (Phytotaxa, 2014)
Lindernia dubia is reported for the first time from India. Its description, illustration, distribution and habitat notes are provided. The taxonomic identity of Lindernia nelliyampathiensis, a recently described new species from India is discussed. Since it is closely matching with L. dubia, here we synonymize L. nelliyampathiensis under L. dubia.